(untitled) (Research, Society and Development, 2020)
Introduction: Immunotherapy with T-CAR cells has been used as an alternative method of treatment for Acute Lymphoid Leukemia (ALL). ALL is a pathology in which there is an exacerbated increase in immature young cells, since its most affected cell precursors are T cells and, in most cases, B cells. The objective of this article was to explain the technique of immunotherapy with cells T-CAR, as well as its operation. Methodology: This is a bibliographic review with a qualitative approach of an exploratory type, of which searches were carried out in the main national and international electronic databases: Pubmed, Eletronic Library On-line (SCIELO) Virtual health library (Bvs), Cell, Science, Nature and Scholar Google from 2007 to 2018. Results: ALL is a pathology that affects the production of blood cells such as erythrocytes, megakaryocytes and granulocytes, this is due to the high spread of blasts in the bone marrow. This disease has conventional treatment mainly chemotherapy and radiotherapy, as well as stem cell transplantation, however these methods can cause several complications to the patient. Therapy with T-CAR cells targets the destruction of the individual’s B cells, through the recognition of specific antigens on these cells (CD19). Conclusion: Treatment with T-CAR cells shows adverse effects of low severity compared to conventional therapies (chemotherapy and radiotherapy). Therefore, this immunotherapy may favor, in the future, a high number of patients fighting not only ALL, but also several other diseases.